Effect Evaluation of Sahtak bi Sahnak, a Lebanese Secondary School-Based Nutrition Intervention: A Cluster Randomised Trial - Said, Liliane; Gubbels, Jessica S.; Kremers, Stef P. J. (Frontiers in Nutrition, 2022)
Objective To evaluate the effectiveness of Sahtak bi Sahnak on dietary knowledge and adherence to dietary guidelines in Lebanese adolescents. Design/setting A cluster randomised controlled trial was conducted in public and private secondary schools located in urban and rural regions in Lebanon. Participants Sixteen secondary schools including 1,572 adolescents were randomly assigned to the intervention (n = 739) or control group (n = 833). Intervention Sahtak bi Sahnak is an educational school-based intervention dedicated to improving dietary adherence to nutritional guidelines, increasing the level of dietary knowledge, and preventing the development of obesity during adolescence. It was systematically designed based on the Intervention Mapping framework. The total length of the intervention was around seven educational sessions, until all of the 11 lessons were covered. Each education session lasted 20–40 min. Main Outcome Measures Dietary knowledge and adherence levels were measured at baseline and post-intervention using validated questionnaires. Statistical Analysis Multivariate multilevel regression models were used to examine intervention effects on outcomes, controlled for background characteristics (i.e., age, gender, location, type of school, grade, BMI z-score). Results The intervention group showed significant improvements in total dietary knowledge (B = 12.74, p < 0.001) and intake of healthy items (B = 1.89, p < 0.001), compared to the control group. Intake of unhealthy items decreased significantly (B = −1.43, p < 0.001), compared to the control group. These results were adjusted for age, gender, type of school, location, BMI z-score, study group, and score at baseline. Conclusion and Implications Sahtak bi Sahnak is an effective and culturally appropriate school-based intervention for targeting diet among a variety of Lebanese adolescents.